Structural and optical properties of GdAlO3:RE3+ (RE = Eu or Tb) prepared by the Pechini method for application as X-ray phosphors - Oliveira, H. H. S. [UNESP]; Cebim, Marco Aurelio [UNESP]; Da Silva, A. A. [UNESP]; Davolos, Marian Rosaly [UNESP] (Elsevier B.V. Sa, 2009)
In this work, GdAlO3:RE3+ (RE = Eu or Tb) was successfully prepared by the Pechini method at lower temperatures when compared to others methods as solid-state synthesis and sol-gel process. In accordance to the XRD data, the fully crystalline single-phase GdAlO3 could be obtained at 900 degrees C. The differential thermal analysis (DTA) shows a crystallization peak at 850 degrees C. The samples are composed by monocrystalline particles (50-120 nm) exhibiting the formation of aggregates among them, which indicates the beginning of the sinterization process. This feature indicates a strong tendency to the formation of aggregates, which is a suitable ability for the close-packing of particles, and hence a potential application in X-ray intensifying screens. Luminescence measurements indicate Gd3+ -> RE3+ energy transfer. The Eu3+ emission spectra exhibit all the characteristics D-5(0) -> F-7(j) transitions and the observed profile suggests that RE3+ ions occupy at least one site without center of symmetry. For terbium-doped samples, the D-5(3) -> F-7(j) (blue emission) and D-5(4) -> F-7(j) (green emission) transitions were observed and the ratio between them may depend on the Tb3+ content due to cross-relaxation processes. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Rare earth alloys and compounds; Chemical synthesis; Optical properties; Luminescence; Optical spectroscopy